ANALISIS DETERMINAN PERINGKAT SUKUK DAN PERINGKAT OBLIGASI DI INDONESIA - Neneng Sudaryanti; Akhmad Affandi Mahfud; Ries Wulandari (Tazkia Islamic Finance and Business Review, 2011)
This study attempts to analyze the determinants of sukuk and bond rating in Indonesia. The purpose of this study is to determine factors influencing sukuk and bond rating using separate test. The study uses financial and non financial ratios such as company growth, firm size, profitability, liquidity, leverage ratio, and sukuk and bond maturity. This study examines corporate sukuk and bond that listed from 2004-2006 (9 sukuk and 15 bonds) at Indonesian Stock Exchange for the period of 2007-2009. This research employs ordinal logistic regression. The result of the study reveales that only firm size variable determines sukuk rating while others are not (growth, profitability, liquidity, leverage ratio and maturity). Firm size, profitability, and maturity influences the bond rating above 5 years while growth, liquidity, and leverage ratio are not significantly influence the bond rating.JEL Classification: E44,G11Key words: sukuk rating,bond rating,ordinal logistic regression